(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
Rhythmic gymnastics classes in early childhood require careful consideration of the psychophysiological characteristics of children aged 3 to 6, particularly their need for play, emotional approval, and imaginative thinking. The most effective way to form sustainable motivation for physical activity is through the integration of physical exercises with role-play and narrative elements, which ensure high engagement of the child in the training process. The effectiveness of the proposed psychological and pedagogical method was evaluated through a pedagogical experiment that included an analysis of motivational involvement, attendance, initiative, and emotional stability in experimental and control groups. The results showed that, in the experimental group, attendance increased by 19.1%, initiative by 72%, and the frequency of positive emotional responses by 87%, compared to minimal changes in the control group. The generalized motivational involvement score (based on parental assessment and pedagogical observation) increased by 1.6 points in the experimental group, while only by 0.4 points in the control group. The application of the Wilcoxon criterion confirmed the statistical significance of the changes (p < 0.05). Observations also revealed a decrease in emotional resistance, growth in independence, emotional stabilization, and improvement in group interaction among children in the experimental group. Thus, the effectiveness of the developed method is confirmed by the improvement of all studied indicators of motivation among children in the training group. Further research in this field should focus on examining the influence of motivational background on the development of physical qualities in preschoolers, as well as on creating adapted versions of the method for early school-age children.